Shear strength of soft clay reinforced with polypropylene column - Anas Mohamad Husian, Kassim (2017)
Granular columns is a technique that has the properties of improving bearing capacity, accelerating the dissipation of excess pore water pressure and reducing settlement in a weak soft soil. This research aims to investigate the role of Polypropylene (PP) column in improving the shear strength and compressibility of soft reconstituted kaolin clay by determining the effects of area replacement ratio, height penetrating ratio and volume replacement ratio of a singular Polypropylene column on the strength characteristics. Reinforced kaolin samples were subjected to Unconfined Compression (UCT) and Unconsolidated Undrained (UU) triaxial tests. The kaolin samples were 50 mm in diameter and 100 mm in height. Using the Polypropylene column reinforcement, with an area replacement ratio of 0.3, 0.5 and 0.8. Samples without the Polypropylene column are the controlled sample, which is having maximum shear strengths of 6.035-7.223 kPa. While for 10.24% area replacement ratio with height penetration ratio of 0.3, the maximum shear strengths are 8.422-11.231 kPa which brings the average maximum improvement of shear strengths of 55.65% compared to that of the controlled samples. As for the column with height penetration ratio of 0.5 and 0.8 with 10.24% area replacement ratio, The maximum shear strengths indicates the values of 8.047-10.462 kPa and 8.048-10.396 kPa respectively which makes the improvement of average maximum shear strengths for both set are 45.073% and 46.494%. Meanwhile, for the samples having 25% area replacement ratio and 0.3 height penetration ratio, the maximum shear strengths are 10.427-13.595 kPa, which indicates an improvement of 88.095% for the average maximum shear strengths. As for height penetrating ratio of 0.5 and 0.8 for 25% area replacement ratio, the maximum shear strengths are 8.432-9.627 and 7.640-8.427 kPa respectively. This brings the of average maximum improvements of shear strengths to 40.346% and 23.247%. UU testing showed that Friction angle φ improvement recorded to be from 1.5 to 17.2 % which shows a noticeable change in improvement.This can be explained by the physical properties of the PP particle and its surface. Cohesion c in the other hand shows a remarkable improvement of 25.9 to 142.9 % due to the smoothness and the unavailability of voids at the surface of PP particles. Deviator stress versus axial strain at failure for 70, 140 and 280 kPa cell pressure were tested to have the range of improvement from 14.7 kPa to 67.9 kPa.In conclusion, Polypropylene column greatly improved the shear strength; and could therefore be implemented in reducing the cost of soil improvement as a replacement for non-renewable materials.